China's Foreign Policy Toward India's Internet Censorship In The Galwan Valley Conflict - Salmiati Salmiati; Asma Amin; Wandi Abbas (Jurnal Ilmu Hubungan Internasional LINO, 2025)
Nowadays, the need for the internet is increasing as seen from China and India as the countries with the world's largest population and the world's largest internet users. In this study, entitled "China's Foreign Policy Toward India's Internet Censorship In The Galwan Valley Conflict", the researcher aims to find out how China's foreign policy strategy responds to internet censorship by India. This study uses the concepts of foreign policy, cyber attack and cyber security. This research is a descriptive research that uses literature studies and utilizes primary and secondary data obtained through interviews, articles, journals, documents, reports and various other media which are analyzed qualitatively. China's response to internet censorship carried out by India is that the internet censorship policy for applications is a discriminatory act that violates WTO regulations and the application of internet censorship abuses WTO exceptions on the basis of national security. So far both countries have focused on border issues in which China's foreign policy is focused on critical border issues with India, preventing total hostilities with India and still making India a partner country. The foreign policy strategy undertaken by China to achieve its national interests with India is to carry out negotiations and consultations through the diplomatic and military of the two countries and until negotiations and consultations regarding the border are still ongoing. Keywords: China, Cyber Attack, Cyber Security, Internet Censorship, India